Identification of promising hybrids and opportunities for rapid selection through trait association, combining ability and gene action in the pearl millet (Pennisetum glaucum(L.) R.Br.) gene pool under rainfed conditions - Pareek, S.; Koraboyana, Vijay Kumar; Sai Krishna, K.; Vemula, Anilkumar K.; Alam, Afroz; Gupta, S.K. (Horizon ePublishing Group, 2025)
The ICRISAT pearl millet B-line gene pool, crucial for Indian NARs partners and private seed companies, was assessed through 218Line × Tester crosses using an alpha-lattice design alongside four hybrid checks. The study explored combining ability, gene action, hybrid selection and accelerated product advancement using trait associations and interdependencies. ANOVA revealed strong genotypic and locationeffects and genotype × environment interactions were significant. Grain yield correlated positively with plant height, panicle length, threshing ratio and days to 50 % flowering. Panicle yield per plot had a strong direct effect (0.962) on grain yield, with very high phenotypic (0.95) and genotypic (0.94) correlations. Key yield traits, including days to 50 % flowering (0.164), plant height (0.491) and panicle length (0.414), influenced grain yield indirectly through panicle yield per plot. Significant genetic variability among parental groups emphasized the role of both additive and non-additive genetic variance. Narrow-sense heritability was highest for productive tillers (84.00 %), days to50 % flowering (65.67 %) and panicle girth (62.81 %). Inbreds ICMR 08888 (2.87), ICMB 10555 (2.81), ICMB 01666 (2.71), ICMB 08888 (2.41) andICMB 11111 (2.16), exhibited strong positive GCA effects for grain yield. Hybrids ICPH213, ICPH265, ICPH273, ICPH321 and ICPH166 exhibited high SCA for grain yield and reduced days to 50 % flowering, indicating superior per-day productivity. A total of seventeen hybrids includingICPH033, ICPH189, ICPH197 and ICPH206, have been identified for large-scale evaluation based on their high yield potential and desirable market-specific traits, such as adaptation to the A1 Zone, medium maturity, dual-purpose suitability, short plant type suited for the BZone, large panicle size and excellent fodder yield. To optimize selection efficiency, “Product Rating Index”, a metric combining flowering duration and grain yield, is proposed for assessing wider adaptability potential. Additionally, prioritizing panicle yield per plot and threshing ratio over direct grain yield measurements is suggested, particularly in early-generation hybrid evaluations.